Type II restriction endonucleases : a historical perspective and more - Pingoud, Alfred; Wilson, Geoffrey G.; Wende, Wolfgang; Justus Liebig University Giessen (My University, 2014)
This article continues the series of Surveys and Summaries on restriction endonucleases (REases) begun this year in Nucleic Acids Research. Here we discuss Type II REases, the kind used for DNA analysis and cloning. We focus on their biochemistry: what they are, what they do, and how they do it. Type II REases are produced by prokaryotes to combat bacteriophages. With extreme accuracy, each recognizes a particular sequence in double-stranded DNA and cleaves at a fixed position within or nearby. The discoveries of these enzymes in the 1970s, and of the uses to which they could be put, have since impacted every corner of the life sciences. They became the enabling tools of molecular biology, genetics and biotechnology, and made analysis at the most fundamental levels routine. Hundreds of different REases have been discovered and are available commercially. Their genes have been cloned, sequenced and overexpressed. Most have been characterized to some extent, but few have been studied in depth. Here, we describe the original discoveries in this field, and the properties of the first Type II REases investigated. We discuss the mechanisms of sequence recognition and catalysis, and the varied oligomeric modes in which Type II REases act. We describe the surprising heterogeneity revealed by comparisons of their sequences and structures.
Keywords: ddc:570